Análise da influência da placa de avanço mandibular nos disturbios de sono através da utilização da polissonografia, questionário de avaliação do sono (SAQ©) e escala de sonolência epworth (ESS-BR) - Castillo, Lourenço Oliveira (2014)
This before - and-after experimental work was carried out to evaluate the influence of a mandibular advancement device for the treatment against sleeping disorders, by comparing the results of the initial and final polysomnography and make an assessment of the improved quality of sleep through the application of polysomnography and sleep quality questionnaire before and after the use of mandibular advancement appliance. Performing correlations between variables of sleep verifying the degree of improvement with the use of mandibular advancement appliance. 19 subjects with a mean age of 39.9 years (SD 12.98) were evaluated before and after the use of mandibular advancement appliance. Was then performed diagnosis by clinical examination, polysomnography and sleep through the SAQ and ESS before using the appliance. After three months, subjects again made polysomnography and answered the SAQ and ESS to assess whether there was an improvement in sleep. To be considered OSAHS, the examination should have an AHI higher than 5 per hour of sleep. The results show there was an improvement in sleep quality, as well as a direct relationship between polysomnography, the ESS- BR and SAQ. Therefore, the mandibular advancement appliance had a positive effect on sleep and did not cause significant side effects in the stomatognathic system in a period of three months